2013
DOI: 10.1002/ajmg.a.36241
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X syndrome: From protein function to therapy

Abstract: Fragile X syndrome (FXS) is the leading monogenic cause of intellectual disability and autism. The FMR1 gene contains a CGG repeat present in the 5'-untranslated region which can be unstable upon transmission to the next generation. The repeat is up to 55 CGGs long in the normal population. In patients with fragile X syndrome (FXS), a repeat length exceeding 200 CGGs generally leads to methylation of the repeat and the promoter region, which is accompanied by silencing of the FMR1 gene. The disease is a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 176 publications
2
57
0
3
Order By: Relevance
“…The ability of (G4C2) 31 repeats to bind eIF2a, a central controller of protein translation, as well as the effects of repeat expression on the subcellular distribution of Pura and FMRP, whose functions in protein translation are well documented (Bagni and Oostra, 2013;White et al, 2009), prompted us to analyze whether (G4C2) 31 is able to affect protein translation. HeLa cells, a well established model to study stress response, were therefore transiently transfected with (G4C2) 31 repeats, and the presence of stress granules, where non-functional translation initiation complexes accumulate in response to stress, was analyzed.…”
Section: (G4c2) 31 Repeats Induce Translational Arrestmentioning
confidence: 99%
“…The ability of (G4C2) 31 repeats to bind eIF2a, a central controller of protein translation, as well as the effects of repeat expression on the subcellular distribution of Pura and FMRP, whose functions in protein translation are well documented (Bagni and Oostra, 2013;White et al, 2009), prompted us to analyze whether (G4C2) 31 is able to affect protein translation. HeLa cells, a well established model to study stress response, were therefore transiently transfected with (G4C2) 31 repeats, and the presence of stress granules, where non-functional translation initiation complexes accumulate in response to stress, was analyzed.…”
Section: (G4c2) 31 Repeats Induce Translational Arrestmentioning
confidence: 99%
“…A number of studies have now reported rescue of multiple phenotypes in Fmr1 knockout animals with mGlu5 receptor-negative allosteric modulator drugs with different selectivity at various points in development and with a range of treatment duration (Michalon et al, 2012). Although the mGlu5 theory of FXS has the most support from genetic and pharmacological rescue studies in mice, a number of other potential treatments have also been proposed, including GABA receptor agonists, minocycline, and lithium (Bagni and Oostra, 2013;Gross et al, 2012;Henderson et al, 2012;King and Jope, 2013). With multiple pharmacological approaches rescuing some brain or behavioral phenotypes in Fmr1 knockout animals, the overall data suggest either multiple pathways toward treatment or a lack of specificity to some of these rescued phenotypes.…”
Section: Rare Simple Genetic Phenocopies Could Reveal New Treatment mentioning
confidence: 99%
“…With the increasing knowledge accumulating on the many functions of the FMRP protein, especially at the synaptic level, numerous pharmacological trials have been performed to try and compensate for the altered function of specific neuronal receptors [reviewed in Bagni and Oostra, 2013]. One of the most advanced clinical trials used a metabotropic glutamate receptor antagonist with promising results [Jacquemont et al, 2011].…”
Section: Transcriptional Therapy Of Fragile X and Other "Epigenetic" mentioning
confidence: 99%
“…All these epigenetic changes result in heterochromatinization of the FMR1 locus [Coffee et al, 2002;Tabolacci et al, 2005Tabolacci et al, , 2008a, preventing transcription and resulting in absence of the FMRP protein. An exhaustive overview of FMRP functions is provided by Bagni and Oostra [2013] in this same issue. Very few FXS patients have deletions or point mutations of the FMR1 gene [DeBoulle et al, 1993;Collins et al, 2010], resulting anyhow in FMRP loss-of-function.…”
Section: Fragile X Syndromementioning
confidence: 99%
See 1 more Smart Citation